"Getting Ready for School:" A Preliminary Evaluation of a Parent-Focused School-Readiness Program. (11th March 2012) - Noble, Kimberly G.; Duch, Helena; Darvique, Maria Eugenia; Grundleger, Alexandra; Rodriguez, Carmen; Landers, Cassie
Abstract : Children from disadvantaged backgrounds tend to start school with fewer school readiness skills than their more advantaged peers. Emergent literacy and math skills play an important role in this gap. The family is essential in helping children build these skills, and the active involvement of families is crucial to the success of any intervention for young children. The Getting Ready for School (GRS) program is a parent-focused curriculum designed to help parents equip their children with the skills and enthusiasm necessary for learning when they start school. Parents meet in weekly workshops led by a trained facilitator and implement the curriculum at home with their children. The objective of this pilot study was to assess the promise of the GRS intervention in children participating in an urban Head Start program and to explore parents' responses to the intervention. We hypothesized that participation in GRS would improve school readiness in literacy and math skills, relative to participation in business-as-usual Head Start. Four Head Start classrooms (two randomly selected "intervention" and two "comparison" classrooms) participated in this study. Preliminary analyses suggest that GRS improves school readiness over and above a Head Start-as-usual experience. Implications for early childhood programs and policies are discussed.